Anatomical Variations of Anterior Ethmoidal Foramen and Cribriform Plate: Relations With Sex. Issue 1 (15th January 2022) - Gibelli, Daniele; Cellina, Michaela; Gibelli, Stefano; Floridi, Chiara; Termine, Giovanni; Sforza, Chiarella
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Position of anterior ethmoidal artery and height of lateral lamella of cribriform plate (LLCP) represent critical variants in endoscopy. In 200 maxillofacial computed tomography scans of patients the position of anterior ethmoidal foramen (AEF) in relation to ethmoid roof was recorded. The height of LLCP was measured and classified according to Keros classification. Differences in AEF position and distribution of Keros types, and LLCP height according to sex were assessed through chi-square test ( P  < 0.05) and 1-way analysis of covariance (ANCOVA) test, respectively ( P  < 0.05). Differences in LLCP height according to different AEF position were assessed through Mann–Whitney test ( P  < 0.05). No differences were observed in prevalence of AEF exposure according to sex ( P  > 0.05); LLCP height was higher in males than in females, with a higher frequency of Keros type 3 ( P  < 0.05). Moreover, subjects with AEF exposure had a significantly higher LLCP height ( P  < 0.01). Results highlighted innovative data useful for improving the knowledge of these sensitive variants.